2004
DOI: 10.1007/s11104-005-0694-0
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of growth reduction of lowland rice caused by a temporary loss of soil-water saturation

Abstract: Decreases in nutrient availability after loss of soil-water saturation are significant constraints to productivity in lowland rainfed rice soils. The effectiveness of soil amendments like lime and straw in ameliorating these constraints are poorly understood. This pot experiment was conducted in Cambodia to investigate changes in soil chemical properties and nutrient uptake by rice after applying lime or straw to continuously flooded or intermittently flooded soil. In continuously flooded soils, exchangeable A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 18 publications
3
21
1
Order By: Relevance
“…A third possibility is that residues increase the availability of soil nutrients. Seng et al (2004) found that when there was a temporary loss of water in flooded rice systems, straw incorporation increased P availability and uptake, increased soil pH, reduced Al toxicity, and increased rice growth. Temporary losses of floodwater are common in rain-fed rice soils (Fukai et al 1998) and were observed in two of the four years at Champassak (Fig.…”
Section: Yield Response To Organic Residues Alonementioning
confidence: 99%
See 1 more Smart Citation
“…A third possibility is that residues increase the availability of soil nutrients. Seng et al (2004) found that when there was a temporary loss of water in flooded rice systems, straw incorporation increased P availability and uptake, increased soil pH, reduced Al toxicity, and increased rice growth. Temporary losses of floodwater are common in rain-fed rice soils (Fukai et al 1998) and were observed in two of the four years at Champassak (Fig.…”
Section: Yield Response To Organic Residues Alonementioning
confidence: 99%
“…Use of organic residues has been shown to enhance nutrient cycling, improve nutrient use efficiency, and increase productivity in rain-fed lowland rice systems in other Southeast Asian countries (Ragland and Boonpuckdee 1988;Willet 1995;Seng et al 2004). Available onfarm residues include rice straw, rice hulls, and farmyard manure (FYM).…”
Section: Introductionmentioning
confidence: 99%
“…These conditions reduce the content of soil organic matter, and increase the immobilization of nutrients such as phosphorus (Seng et al 2004;Zhou et al 2014). Phosphorus is one of the nutrients limiting plant productivity, because of its essential role in the process of flowering and seed formation.…”
Section: Introductionmentioning
confidence: 99%
“…plant height) and dry matter production under non-flooded condition were suppressed compared with shallow water condition, even though there were no remarkable declines in soil water content and no clear drought symptoms such as leaf rolling in non-flooded condition. P and Fe became less available, and Al more available in aerobic non-flooded condition compared with reduced condition under flooding (Takenaga 1995;Seng et al 2001b), which would have negative effects on rice growth on P deficient Cambodian paddy soils (White et al 1997;Seng et al 2002Seng et al , 2004. Recovery growth after transplanting shock may have been slower under nonflooded condition than shallow flooded condition, resulting in less vigorous vegetative growth (Ikeda et al 2007).…”
Section: Effect Of Water Conditionsmentioning
confidence: 99%